2019
DOI: 10.3122/jabfm.2019.06.190121
|View full text |Cite
|
Sign up to set email alerts
|

Use of Advance Care Planning Billing Codes in a Tertiary Care Center Setting

Abstract: Introduction: The Centers for Medicare and Medicaid Services released the final payment rules for reimbursement of advance care planning (ACP) effective January 2016. In its first year, 23,000 providers nationwide submitted 624,000 claims using the Current Procedural Terminology codes 99497 and 99498. The objectives of our study were to 1) assess the frequency of ACP codes used at a single academic tertiary care center in Iowa, 2) determine when and by whom the codes were used, and 3) summarize ACP clinical no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…ACP may occur either outside of the clinician–patient relationship, or within it but not be captured by billing. Indeed, our own unpublished qualitative work has demonstrated that much ACP occurs in clinical settings without being billed 3 . Despite these limitations, because Medicare claims represent a standardized measure of ACP services in a very large and rich national dataset, it offers an advantage over previous studies that may have relied on small samples or nonstandardized measures of ACP.…”
Section: Introductionmentioning
confidence: 99%
“…ACP may occur either outside of the clinician–patient relationship, or within it but not be captured by billing. Indeed, our own unpublished qualitative work has demonstrated that much ACP occurs in clinical settings without being billed 3 . Despite these limitations, because Medicare claims represent a standardized measure of ACP services in a very large and rich national dataset, it offers an advantage over previous studies that may have relied on small samples or nonstandardized measures of ACP.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 12 summarized the content of ACP clinical notes and compared with ACP billing code reimbursement in a tertiary care setting, one of the many places it would seem obvious to initiate these types of interactions. They reported very low use of ACP billing, suggesting that the reimbursement level continues to be insufficient to make ACP financially worthwhile.…”
Section: End-of-life Care and Advance-care Planningmentioning
confidence: 99%